2002
DOI: 10.1242/jcs.115.15.3207
|View full text |Cite
|
Sign up to set email alerts
|

NUANCE, a giant protein connecting the nucleus and actin cytoskeleton

Abstract: NUANCE (NUcleus and ActiN Connecting Element) was identified as a novel protein with an α-actinin-like actin-binding domain. A human 21.8 kb cDNA of NUANCE spreads over 373 kb on chromosome 14q22.1-q22.3. The cDNA sequence predicts a 796 kDa protein with an N-terminal actin-binding domain, a central coiled-coil rod domain and a predicted C-terminal transmembrane domain. High levels of NUANCE mRNA were detected in the kidney, liver,stomach, placenta, spleen, lymphatic nodes and peripheral blood lymphocytes. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 254 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…The LINC complex physically connects the cytoskeleton to the nucleus and transmits mechanical forces from the cytoskeleton across the NE to the nucleoskeleton (Figure 3) [132,133]. The LINC complex has been implicated in cell division [134], cytoskeletal organization [135], and organelle positioning [136], showing its importance for basic cellular functions. The ONM components of the LINC complex are the nesprins, a large family of spectrin-repeat transmembrane proteins [135,137], which bind to the cytoskeleton via actin or microtubules [135,138].…”
Section: The Linc Complex Nesprins and Sun Domain Proteinsmentioning
confidence: 99%
“…The LINC complex physically connects the cytoskeleton to the nucleus and transmits mechanical forces from the cytoskeleton across the NE to the nucleoskeleton (Figure 3) [132,133]. The LINC complex has been implicated in cell division [134], cytoskeletal organization [135], and organelle positioning [136], showing its importance for basic cellular functions. The ONM components of the LINC complex are the nesprins, a large family of spectrin-repeat transmembrane proteins [135,137], which bind to the cytoskeleton via actin or microtubules [135,138].…”
Section: The Linc Complex Nesprins and Sun Domain Proteinsmentioning
confidence: 99%
“…In comparison to parental control LCLs, the analyses of the patient indicated that the p.(E788K) and p.(V828G) mutations do not affect the nuclear targeting of mutant proteins. This is not surprising based on the consideration that the mutations reside within the nesprin-2 giant N-terminal half (SR5) and not in the C-terminal KASH domain, which mediates nuclear envelope targeting [1,2,6]. Although SYNE2 transcript expression in the patient LCLs is unaffected, the amount of nesprin-2 giant protein is significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Primary antibodies used: affinity-purified nesprin-2 CT (pAbK1, [14]), dilution 1:500 (IF) and 1:1500 (WB); mouse anti-nesprin-2 giant (clone K20-478, [6]), undiluted (IF); and mouse anti-GAPDH (Proteintech, Manchester, UK), dilution 1:10,000 (WB). Indirect IF analysis involved secondary chicken anti-Rabbit IgG conjugated Alexa Fluor 488, goat anti-Rabbit Alexa Fluor 568, and donkey anti-mouse Alexa Fluor 488 antibodies (ThermoFisher Scientific, Loughborough, UK, diluted 1:1000).…”
Section: Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations